The Ascension of the Apostle and the Heavenly Book - Widengren, Geo (2000)
= Acta Universitatis Upsaliensis 1950: 7; Daraus: I. Mesopotamian Religion 7-21; parṣu 86-91; Schlussvokale im frühen Neubabylonisch 92-3; dudittu 98-100.